2010
DOI: 10.1139/v09-164
|View full text |Cite
|
Sign up to set email alerts
|

Rate constants for decarboxylation reactions calculated using no barrier theory

Abstract: No barrier theory (NBT) provides both a qualitative way of thinking about what makes a reaction fast or slow and a quantitative way of calculating the rate constant (free energy of activation) corresponding to a particular mechanism. The origin and development of this idea are reviewed and examples of its use for qualitative understanding are presented before applying it to a set of decarboxylations. From the literature, a set of best values for rate constants for decarboxylation was picked. Detailed mechanist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 107 publications
2
24
0
Order By: Relevance
“…Cyclohexanone enol has a pK a of 11.70 while 3‐hydroxy‐2‐cyclohexen‐1‐one (the enol of 1,3‐cyclohexanedione) has a pK a of 4.34, for a difference of 7.4. The pK a of the enol of a carboxylic acid ester is approximately 6; the effect of conjugation to an ester may well be smaller than for conjugation to a ketone so that the expected pK a for Meldrum's enol would be somewhat greater than −1.4, consistent with the value of 1.9 obtained above. The enol content of dialkyl malonate is unknown, but Graham and Williams suggested that it is near pK E = 11, based on the assumption of diffusion control for a reaction known to be close to diffusion control.…”
Section: Resultssupporting
confidence: 77%
“…Cyclohexanone enol has a pK a of 11.70 while 3‐hydroxy‐2‐cyclohexen‐1‐one (the enol of 1,3‐cyclohexanedione) has a pK a of 4.34, for a difference of 7.4. The pK a of the enol of a carboxylic acid ester is approximately 6; the effect of conjugation to an ester may well be smaller than for conjugation to a ketone so that the expected pK a for Meldrum's enol would be somewhat greater than −1.4, consistent with the value of 1.9 obtained above. The enol content of dialkyl malonate is unknown, but Graham and Williams suggested that it is near pK E = 11, based on the assumption of diffusion control for a reaction known to be close to diffusion control.…”
Section: Resultssupporting
confidence: 77%
“…Decarboxylation of beta-keto acids, by itself, is an important reaction in connection with catalysis by enzymes, the mechanism of which has been debated for almost a century [21,22]. The reaction has been extensively studied in a solution [23][24][25][26][27], and in the gas phase [28].…”
Section: Introductionmentioning
confidence: 99%
“…Guthrie in his No Barrier Theory analysis of the beta-keto acids decarboxylation has discussed the most energy demanding electronic and structural changes required to occur when going through the transition state [23,27]. They include stretching C-C bond, changing hybridization of the carboxylic carbon from sp 2 to sp, that of the alpha carbon from sp 3 to sp 2 , and transferring the proton.…”
Section: Introductionmentioning
confidence: 99%
“…No Barrier Theory proposes that for a simple process, there is no kinetic barrier but simply a quadratic potential. A simple process is defined as one for which the energy is a quadratic function of a suitable progress variable The kinetic barriers that are observed for essentially all real chemical reactions result from the need for more than one simple process to occur more or less simultaneously for the overall reaction to take place.…”
Section: Resultsmentioning
confidence: 99%
“…We have computed the thermodynamic properties of nitriles, imidic acids, and amides studied in this work and, from these, the equilibrium free energies of reaction for both stages of nitrile hydrolysis. We wish to report that the rate constants for nitrile hydrolysis in acid or base have been calculated using No Barrier Theory (NBT), leading to the computed rate constants in satisfactory agreement with experiment. These calculations cover the range of reactivity thus far reported.…”
Section: Introductionmentioning
confidence: 87%